EPEN-50. THE MANAGEMENT AND TREATMENT OF PEDIATRIC SPINAL CORD EPENDYMOMA: RESULTS FROM A COLLABORATIVE INTERNATIONAL MULTI-INSTITUTIONAL REVIEW. (4th December 2020) - Lucas, John; Kumirova, Ella; Tsang, Derek; Vinitsky, Anna; Chiang, Jason; Hazrati, Lili-Naz; Lane, Shelby; Agbahiwe, Harold; Upadhyay, Santhosh; Tinkle, Christopher; Konovalov, Dmitry; El-Ayadi, Moatasem; et al.
Abstract: PURPOSE: Pediatric Spinal cord ependymoma (SCE) is rare, and the management is often heterogeneous across centers. We evaluated the impact of clinical, pathologic, and treatment-related factors on outcomes in a multi-institutional, international cohort. METHODS: SCE patients age <21 years were reviewed across 5 institutions. We utilized nonparametric descriptive statistics, survival, and recursive partitioning analysis (RPA) to examine patient, tumor, histopathologic and treatment characteristics, failure pattern, and cause of death. RESULTS: 125 patients were identified, 18 (14.4%) with metastases. Initial surgery was GTR, and STR in 44, 56% of patients respectively. Histology was grade 1, 2, and 3 in 55, 17.7 and 23.2% respectively. 55 patients with initial GTR were observed (52.7%) or irradiated (43.6%); 60 patients had STR and were observed (40%) or irradiated (60%). The 7-year event-free (EFS) and overall survival (OS) was 60% (95% CI 51.5–71.4) and 79% (95% CI 71.1–87.8) respectively. STR and metastasis increased the hazard for death [HR 1.87, 95% CI 1.02–3.57, p=0.05 (vs. GTR)] and [HR 2.28, 95% CI 1.1–5.2, p=0.048 (vs. localized)] respectively. Across 43 failures, local failure predominated (48.8%). Distant and combined failure occurred in 30.2 and 13.9% respectively. Adjuvant RT offered a 20% absolute improvement (vs. observation) in EFS at 5 years regardless of extent of resection. RPA identified thoracic (vs. non-thoracic), grade (1 & 3 vs. 2), STR (vs. GTR) and metastases as determinants of inferior EFS. CONCLUSIONS: Tumor and treatment-related factors are predictive of EFS. OS is favorable despite diverse schema and frequent distant failures.